Advanced control of a continuous oscillatory flow crystalliser. (October 2017) - Tahir, F.; Krzemieniewska-Nandwani, K.; Mack, J.; Lovett, D.; Siddique, H.; Mabbott, F.; Raval, V.; Houson, I.; Florence, A.
Abstract: This paper presents the application and challenges of achieving Model Predictive Control (MPC) on two continuous oscillatory baffled crystallisation reactors, delivering precise product quality control in the face of raw material fluctuations. A key advantage of MPC is that it effectively deals with multivariable interactions and constraints that appear within the continuous crystallisation process. Using a flexible real-time software package, a control scheme is proposed that incorporates three MPC blocks for controlling reactor cooling profile, API (Active Pharmaceutical Ingredient) concentration and crystal size distribution, respectively. Furthermore, the solution is customisable and transferable to different crystallisation reactors as well as various APIs.